Rapporter - Frandsen Skjelbo, Johannes; Holme Hansen, Thomas; Kaargaard Nielsen, Steen; Fjeldsøe, Michael; Pedersen, Peder Kaj; Bonde, Lars Ole; Hesselager, Jens (Danish Yearbook of Musicology, 2012)
Research Projects Popular Music and Muslim Youth (Johannes Frandsen Skjelbo) Researching Music Censorship (RMC) (Annemette Kirkegaard) Conferences Musics Cultures Identities – 19th Congress of the International Musicological Society (IMS), Rome, July 2012 (Thomas Holme Hansen) Seventh International Conference on Music since 1900 & Lancaster University Music Analysis Conference, Lancaster, July 2011 (Steen Kaargaard Nielsen) Carl Nielsen: Inheritance and Legacy, Copenhagen, November 2011 (Michael Fjeldsøe) 16th Nordic Musicological Congress, Stockholm, August 2012 (Peder Kaj Pedersen) Music and Public Health, Copenhagen, November 2011 (Lars Ole Bonde) Danish Musicological Society, 2011/2012 (Jens Hesselager)